2022
DOI: 10.3389/fvets.2022.846981
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Heat Stress Resistance During Spermatogenesis in Turpan Black Sheep

Abstract: Heat stress can affect the reproductive function of livestock and cause harm to animal production, which can seriously damage the economic interests of livestock producers. Therefore, it is important to explore the effect of heat stress on reproductive function to improve livestock production. In this study, the experimental animals Turpan black sheep and Suffolk sheep were selected as controls, each with 10 sheep, and the reproductive physiological performance was measured in Turpan, China from April to Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The challenge of global warming and the resulting negative effects of heat stress on animal health and productivity reinforce the need for intensive research to identify animal species and breeds with greater thermal adaptation (17,18). Profound impact of heat stress on the immune system has been reported for several animal species (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The challenge of global warming and the resulting negative effects of heat stress on animal health and productivity reinforce the need for intensive research to identify animal species and breeds with greater thermal adaptation (17,18). Profound impact of heat stress on the immune system has been reported for several animal species (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…By using an animal model or scrotal insulation, many studies have demonstrated the adverse influence of heat stress on spermatogenesis, semen quality, and reproductive traits in bovine [27], mice [28], dogs [29], sheep [30], and boar [7] when exposed to heat stress environment. However, few studies focus on the effect of in vitro exposure of semen to heat stress on sperm quality and functionality.…”
Section: Effect Of Temperature Changes During Delivery On Sperm Quali...mentioning
confidence: 99%
“…There are many common thermogenic factors that affect scrotal temperature, including lifestyle and behavioral influences, occupational and environmental factors, and pathophysiological causes [ 24 ]. Spermatogenesis is a temperature-dependent process, and any increase above the normal scrotal temperature range can result in the death of heat-vulnerable germ cells and disrupted somatic cell function [ 25 ].…”
Section: Introductionmentioning
confidence: 99%